Convenient and Reliable Routes Towards 2‐Aminothiazoles: Palladium‐Catalyzed versus Copper‐Catalyzed Aminations of Halothiazoles. Issue 16 (11th November 2013) - Toulot, Stéphanie; Heinrich, Timo; Leroux, Frédéric R.
Abstract Two efficient methods for the amination of 2‐halothiazoles are presented here. A first protocol requires a Pd/L system. Several 2‐aminothiazoles were synthesized under optimized conditions and isolated in good yields. The first palladium‐catalyzed CN coupling reactions between 2‐halothiazoles and primary alkylamines are presented. In a second part, ligand‐free copper‐catalyzed aminations of 2‐halothiazoles by alkylamines and aniline in a green solvent have been developed. The protocol is very effective for primary and secondary amines and perfectly tolerates the presence of another halide moiety on the 2‐halothiazole. The reaction occurs under the assistance of microwave irradiation, which drastically decreases the reaction time. The reaction leads to the formation of 2‐aminothiazoles, key molecules in pharmaceutical research. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>